Exit duration and unemployment determinants for Korean graduates - Jung-Yon Lim; Young-Min Lee (Journal for Labour Market Research, 2019)
PurposeThis study aims to resolve Korea's youth unemployment problem by analyzing the exit duration and unemployment determinants for college graduates in Korea. More specifically, it identifies the factors that improve young people's employability by examining the impact of individual and college characteristics, employment preparation behavior, self-esteem, and job-seeking activities during college on reducing unemployment.Design/methodology/approachData from the eighth to 11th Korean Education and Employment Panel surveys are compiled and analyzed. A survival analysis and Cox proportional hazards model are used. Survival analysis is a useful statistical method for data analysis to describe, explain, or predict the occurrence and timing of a particular event.FindingsCollege graduates differ in their employment preparation behavior based on their individual and college characteristics. Women focus more on achieving a good grade point average. Men are more active in seeking jobs, with the type of college and major subjects affecting their participation in on-the-job training. Second, the longer a college graduate's unemployment exit duration is, the less likely it becomes that he or she will escape from unemployment. Third, self-esteem is an important factor in increasing the likelihood of escaping from unemployment. Fourth, while job-seeking activities have a positive effect on escaping unemployment, excessive employment preparation behavior has a negative effect.Originality/valueThe paper deals with a serious problematic situation of Korea's youth unemployment. Significant results were identified and several research implications were proposed to make potential contributions for future research on youth unemployment.
Keywords: E24; I28; J13; O15; 330; Korean Education and Employment Panel; Survival analysis; Unemployment exit duration; Youth unemployment